A Novel Stilbene Analogue: Antioxidant Activity and Application in Controlling the Quality and Bacterial Growth of Shrimp Refrigerated at 4ºC. Issue 2 (7th February 2022) - Xia, Wei; Chakka, Vara Prasad; Chen, Kai; Wang, Fan; Xie, Yuan-Yuan; Hider, Robert C.; Zhou, Tao
ABSTRACT: The antioxidant potential of a novel stilbene analogue (5-hydroxy-2-[2-(3, 5-dihydroxy-phenyl)-vinyl]-1-hexyl-pyridin-4-one) (named SA ) along with its application in shrimp refrigeration was investigated. The antioxidant activity of SA was evaluated by determining the radical scavenging ability. Further, the shrimp preservative efficacy of SA was investigated on Penaeus vannamei stored at 4°C by determining the quality indicators. The shelf life of shrimp treated with SA was extended to 10 days, while the shelf life of shrimp treated with 4-hexylresorcinol (4-HR), kojic acid, and sterile saline was 9, 6, and 4 days, respectively. The shelf life of shrimp was further extended to 12 days when treated with SA in combination with 0.1% citric acid. The residue of SA in shrimp was found to be extremely low even after 12 days of storage. Furthermore, MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay indicated that SA was nontoxic to two cell lines. SA could find application in shrimp refrigeration.